Mental health problems in children with intellectual disability. (June 2022) - Totsika, Vasiliki; Liew, Ashley; Absoud, Michael; Adnams, Colleen; Emerson, Eric
Summary: Intellectual disability ranks in the top ten causes of disease burden globally and is the top cause in children younger than 5 years. 2–3% of children have an intellectual disability, and about 15% of children present with differences consistent with an intellectual disability (ie, global developmental delay and borderline intellectual functioning). In this Review, we discuss the prevalence of mental health problems, interventions to address these, and issues of access to treatment and services. Where possible, we take a global perspective, given most children with intellectual disability live in low-income and middle-income countries. Approximately 40% of children with intellectual disability present with a diagnosable mental disorder, a rate that is at least double that in children without intellectual disability. Most risk factors for poor mental health and barriers to accessing support are not unique to people with intellectual disability. With proportionate universalism as the guiding principle for reducing poor mental health at scale, we discuss four directions for addressing the mental health inequity in intellectual disability.